2010
DOI: 10.1007/s00063-010-1084-9
|View full text |Cite
|
Sign up to set email alerts
|

Paresen, Myalgien und massive CK-Erhöhung: eine schwere neurologische Erkrankung?

Abstract: Transient pareses, myalgias, and creatine kinase elevation can indicate primary aldosteronism among hypertensive patients. If clinically suspected, the aldosterone-renin ratio should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…It is also reported that elevation of CK may be present in Conn's syndrome 45. In our patient, there was an ongoing and increasing muscle weakness.…”
supporting
confidence: 62%
“…It is also reported that elevation of CK may be present in Conn's syndrome 45. In our patient, there was an ongoing and increasing muscle weakness.…”
supporting
confidence: 62%